The Effect of Word Mapping Strategy in Teaching Vocabulary for Class VI Students of SD Negeri 18 Bengkulu City - Tamara, Veni (Journal of Primary Education, 2025)
This research aims to determine the effectiveness of the Word Mapping Strategy on students' understanding mastery at SDN 18 Bengkulu City, as observed by seventh-grade students at SDN 18 Bengkulu City. The method employed in this research is a quantitative approach with an experimental design. The population of this study was students at SDN 18, Bengkulu City. This research was conducted with two groups, namely the experimental class using the Word Mapping Strategy and the control class without using the Word Mapping Strategy. First, the researcher gave a pre-test to both classes. After that, the researcher gave a post-test to both classes. Pre-test and post-test scores are collected from multiple-choice tests. Then analyzed using the SPSS 26 window. The findings of this research indicate that teaching and learning using the Word Mapping Strategy is effective. The average score of the experimental class from the pre-test was 50,4, and the post-test was 76,9. This is proven by the t-count value (5.094), which is greater than the table at the 5% significance level. Next, the hypothesis test obtained a 2-tailed sig (p of 0.00 while alpha (a) was 0.05 (0.00<0.05). So, the effect of the Word Mapping Strategy in teaching comprehension has a significant effect on students' mastery. The magnitude of the effect obtained is based on the ANCOVA test, obtained from the count < f table. So it is concluded that it has an influence, for as large an influence as the percentage of influence can be seen in the partial eta squared column table, the effect is 0.058 or 58%.